Challenges for Regulating Tort Liability for Adaptive Robots: An Analytical Study - Mahmoud Ibrahim Fayyad,; Ibrahim Khaled Yahya, (Journal of Legal Sciences, 2024)
This research paper unequivocally supports arguments seeking to establish a connection between the actions of an adaptive robot and those of a human being. It does not assert personal responsibility on the part of the robot; rather, it highlights the challenges associated with traditional theories in assigning responsibility to humans. Furthermore, the paper examines how modern theories aimed at overcoming the limitations of traditional approaches have not only failed to introduce new solutions but have also inherited their drawbacks.In addressing these issues, the paper offers justifications for rejecting robots' personal responsibility, whether legal or illegal, by intertwining them with the moral and psychological aspects of responsibility within the legal framework. Subsequently, the paper proposes a robust legal foundation that sidesteps the pitfalls of existing theories, providing a more comprehensive perspective on regulating tort liability for adaptive robots.